2016
DOI: 10.1523/jneurosci.3600-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Protein Kinase Mζ in the Hippocampus Enhances Long-Term Potentiation and Long-Term Contextual But Not Cued Fear Memory in Rats

Abstract: The persistently active protein kinase M (PKM) has been found to be involved in the formation and maintenance of long-term memory. Most of the studies investigating PKM, however, have used either putatively unselective inhibitors or conventional knock-out animal models in which compensatory mechanisms may occur. Here, we overexpressed an active form of PKM in rat hippocampus, a structure highly involved in memory formation, and embedded in several neural networks. We investigated PKM's influence on synaptic pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 72 publications
5
14
1
Order By: Relevance
“…Data (mean Ϯ SEM) are presented as DI during TR, RA, TEST1, and TEST2, n ϭ 9 per group. upstream PKM to modulate hippocampal AMPAR synaptic insertion, in agreement with findings showing that ORM reconsolidation induces synaptic potentiation in the hippocampus (Clarke et al, 2010) and that BDNF facilitates LTP in the absence of protein synthesis through PKM (Mei et al, 2011;Schuette et al, 2016). Therefore, our results should not be generalized to indicate that all memories are sensitive to PKM inhibition only when reactivated.…”
Section: Discussionsupporting
confidence: 90%
“…Data (mean Ϯ SEM) are presented as DI during TR, RA, TEST1, and TEST2, n ϭ 9 per group. upstream PKM to modulate hippocampal AMPAR synaptic insertion, in agreement with findings showing that ORM reconsolidation induces synaptic potentiation in the hippocampus (Clarke et al, 2010) and that BDNF facilitates LTP in the absence of protein synthesis through PKM (Mei et al, 2011;Schuette et al, 2016). Therefore, our results should not be generalized to indicate that all memories are sensitive to PKM inhibition only when reactivated.…”
Section: Discussionsupporting
confidence: 90%
“…2a ) as expected but that LTP and memory were also increased , contrary to the prediction of occlusion (Fig. 2b, c ) [ 28 ] (for similar effects see [ 26 ]). On the basis of this failure of occlusion, it was concluded that PKM-zeta is not critical for maintenance but is instead a modulator of LTP [ 28 ].…”
Section: Introductionsupporting
confidence: 77%
“…For long‐term potentiation (LTP) induction, a high‐frequency stimulation (HFS) was used consisting of 100 Hz trains of 1‐s duration repeated five times with a 30‐s inter‐train interval (Schuette, Fernandez‐Fernandez, Lamla, Rosenbrock, & Hobson, ). The stimulus intensity was also set to ≈40% of its asymptotic values.…”
Section: Methodsmentioning
confidence: 99%